Institutional ownership and cost of debt: evidence from Thailand - Yordying Thanatawee (Cogent Business & Management, 2023)
This article aims to investigate whether institutional investors aid in lowering the cost of debt using a sample of 311 nonfinancial firms listed on the Stock Exchange of Thailand (SET) over 2011-2020. All data were obtained from the SETSMART database. Controlling for firm characteristics, industry effect, and year effect, we analyze the link between institutional ownership and the cost of debt using pooled ordinary least squares and fixed effects models and find that institutional ownership has a negative relationship with the cost of debt in both models. The fixed effects model also shows that profitability, growth potential, and operating cash flow negatively affect the cost of debt while financial leverage and asset tangibility positively affect the cost of debt. Additionally, the dynamic GMM model indicates that the connection between institutional holdings and debt expenses is significantly negative. Overall, the results suggest that institutional investors provide effective oversight that decreases conflicts between management and lenders, ultimately cutting the cost of borrowing for listed companies in Thailand. In addition, our supplementary analysis suggests that institutional investors must possess a sizeable proportion of shares (at least 23%) to actively perform monitoring duties.
Keywords: G23; G32; G34; 650; Agency Problem; Corporate Governance; Cost of Debt; Institutional Ownership; Monitoring; Thailand